"Women fear the law more than abusers": a study of public trust in health and legal response to violence against women in Santo André, São Paulo State, Brazil - Dabney P. Evans; Casey D. Xavier Hall; Nancy DeSousa; Jasmine D. Wilkins; Ellen Dias de Oliveira Chiang; Maria A. F. Vertamatti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: Little is known about how perceptions of government affects women's views of violence against women. This qualitative study examines women's perceptions of violence against women laws and trust in the health and legal sector response in São Paulo State, Brazil. Thirty interviews with female residents of Santo André, 18 years and older, were audio recorded, transcribed, coded, and analyzed for themes using MAXQDA12 software. All women were familiar with at least one federal violence against women law. They expressed widespread lack of trust in the government. They viewed the legal sector as ineffective and felt violence against women laws have little impact, or exacerbate violence. Disdain for the health sector was less prominent than for the legal sector. A generalized lack of trust in government manifests as a lack of confidence in these laws for women seeking support through legal and health sectors. Adoption of legal protections for women is a significant accomplishment. However, health and legal sector violence against women response needs to consider perceptions of government, how violence against women laws are operationalized, and the role of each sector in ensuring women's safety. Violence against women response efforts should include standardized intersectoral procedures including referral to accessible resources and means of screening women who may be at high risk for femicide.